Muscarinic M4 Receptors on Cholinergic and Dopamine D1 Receptor-Expressing Neurons Have Opposing Functionality for Positive Reinforcement and Influence Impulsivity - Klawonn, Anna M.; Wilhelms, Daniel B.; Lindström, Sarah H.; Singh, Anand Kumar; Jaarola, Maarit; Wess, Jürgen; Fritz, Michael; Engblom, David (Frontiers in Molecular Neuroscience, 2018)
The neurotransmitter acetylcholine has been implicated in reward learning and drug addiction. However, the roles of the various cholinergic receptor subtypes on different neuron populations remain elusive. Here we study the function of muscarinic M4 receptors (M4Rs) in dopamine D1 receptor (D1R) expressing neurons and cholinergic neurons (expressing choline acetyltransferase; ChAT), during various reward-enforced behaviors and in a "waiting"-impulsivity test. We applied cell-type-specific gene deletions targeting M4Rs in D1RCre or ChATCre mice. Mice lacking M4Rs in D1R-neurons displayed greater cocaine seeking and drug-primed reinstatement than their littermate controls in a Pavlovian conditioned place preference paradigm. Furthermore, the M4R-D1RCre mice initiated significantly more premature responses in the 5-choice-serial-reaction-time-task than their littermate controls, indicating impaired waiting impulse control. In contrast, mice lacking M4Rs in cholinergic neurons did not acquire cocaine Pavlovian conditioning. The M4R-ChATCre mice were also unable to learn positive reinforcement to either natural reward or cocaine in an operant runway paradigm. Immediate early gene expression (cFos and FosB) induced by repeated cocaine injections was significantly increased in the forebrain of M4R-D1RCre mice, whereas it remained normal in the M4R-ChatCre mice. Our study illustrates that muscarinic M4Rs on specific neural populations, either cholinergic or D1R-expressing, are pivotal for learning processes related to both natural reward and drugs of abuse, with opposing functionality. Furthermore, we found that neurons expressing both M4Rs and D1Rs are important for signaling impulse control.